Real Interest Rates, Real Exchange Rates, and Net Foreign Assets in the Adjustment Process - Helbling, Thomas (IMF Working Papers; Working Paper ;, 1995)
This paper analyzes the recent behavior of real exchange rates, the trade balance and the net foreign asset position of the United States in an intertemporal optimizing model of the world economy that incorporates heterogeneity across countries and imperfect international capital and good markets. While the model successfully tracks the dynamics of trade balances and net foreign assets it generates too much consumption smoothing and excessively volatile relative prices. Resolving these inadequacies simultaneously is difficult as the elasticity of substitution between tradables and nontradables affects in opposite ways the degree of consumption smoothing and the volatility of relative prices.